2020
DOI: 10.1186/s12957-020-01975-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical basigin expression level in thyroid cancer tissues

Abstract: Background: Thyroid cancer (TC) is the most common endocrine malignancy; basigin (also known as BSG) plays a crucial role in tumor cell invasion, metastasis, and angiogenesis. This study was designed to identify the change of BSG expression in TC and its possible potential mechanism. Methods: The BSG expression levels in TC were demonstrated using data collected from in-house immunohistochemical (IHC), RNA-sequencing (RNA-seq), microarrays, and literatures. Integrated analysis was performed to determined BSG e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…With the emerging understanding of molecular genetics in thyroid cancer, several specific molecular events in PTC have been identified that assist in the diagnosis and prognostic evaluation of PTC patients [11][12][13]. The Btype Raf kinase (BRAF) V600E mutation was found to be the most important candidate biomarker for PTC diagnosis because of its high prevalence and high specificity [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…With the emerging understanding of molecular genetics in thyroid cancer, several specific molecular events in PTC have been identified that assist in the diagnosis and prognostic evaluation of PTC patients [11][12][13]. The Btype Raf kinase (BRAF) V600E mutation was found to be the most important candidate biomarker for PTC diagnosis because of its high prevalence and high specificity [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…We simulated the activation trajectory of ENDO cells and detected the specific deletions of reactive ENDO in PD, especially in the subset of cells of Bsg High . Bsg plays a crucial role in angiogenesis, and its co-expressed genes tended to be enriched in gene terms of the extracellular matrix, cell adhesion and cell-cell interactions [66]. We hypothesized that the loss of ENDO cells in PD resulted in the destruction of tight junctions between cells, thus enhancing the permeability of BBB and promoting the entry of MPP + toxins into the brain environment.…”
Section: Discussionmentioning
confidence: 99%
“…We simulated the activation trajectory of ENDO cells and detected the specific deletions of reactive ENDO in PD, especially in the subset of cells of Bsg High . Bsg plays a crucial role in angiogenesis, and its co-expressed genes tended to be enriched in gene terms of the extracellular matrix, cell adhesion, and cell-cell interactions 67 . We hypothesized that the loss of ENDO cells in PD resulted in the destruction of tight junctions between cells, thus enhancing the permeability of BBB and promoting the entry of MPP + toxins into brain environment.…”
Section: Discussionmentioning
confidence: 99%